2007
DOI: 10.1002/polb.21183
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of silver nanoparticles within an amphiphilic graft copolymer film

Abstract: Silver nanoparticles were prepared by UV irradiation from silver salts, such as AgBF4 or AgNO3, when dissolved in an amphiphilic film of poly((oxyethylene)9 methacrylate)‐graft‐poly((dimethyl siloxane)n methacrylate), POEM‐g‐mPDMS. The in situ formation of silver nanoparticles in the graft copolymer film was confirmed by transmission electron microscopy (TEM), UV‐visible spectroscopy, and wide angle X‐ray scattering (WAXS). The results demonstrated that the use of AgBF4 yielded silver nanoparticles with a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…It has been shown that the Ag 3d 5/2 regions of the XPS spectra for Ag nanocomposite films are very vulnerable to the chemical environment surrounding the Ag species where it is shifted to lower BE when there is strong coordination 60, 61. Just recently, the Ag 3d 5/2 spectra of AgNP (with AgNO 3 as the precursor) formed in situ after UV irradiation within an amphiphilic graft polymer containing ethylene oxide groups has been reported to be at a BE of 368.7 eV, whereas from pure AgNO 3 the BE is at 370.3 eV 62. Furthermore, Wang et.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the Ag 3d 5/2 regions of the XPS spectra for Ag nanocomposite films are very vulnerable to the chemical environment surrounding the Ag species where it is shifted to lower BE when there is strong coordination 60, 61. Just recently, the Ag 3d 5/2 spectra of AgNP (with AgNO 3 as the precursor) formed in situ after UV irradiation within an amphiphilic graft polymer containing ethylene oxide groups has been reported to be at a BE of 368.7 eV, whereas from pure AgNO 3 the BE is at 370.3 eV 62. Furthermore, Wang et.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to microstructural changes, the nanostructural changes in the membranes as a result of the addition of silica were also investigated using SAXS analysis. SAXS is a well-established experimental technique to complement the structural analysis obtained from microscopy images because it provides information over a large sample area [25,26]. The SAXS profiles of the nanocomposite membranes with different MPTMS concentrations are plotted against the scattering vector, q, in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well known that the ether oxygens of the PECH domains are complexed to metal ions via direct coordinative interaction. 28,29 On the other hand, the PS domains are expected not to confine silver ions because of relatively weaker interaction strength of silver ions with aromatic C=C bonds of styrene. Thus most of the salts would be selectively confined and reduced in the hydrophilic PECH domains.…”
Section: Resultsmentioning
confidence: 99%